2015
DOI: 10.1270/jsbbs.65.411
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of seed storability using two different populations with a same parent rice cultivar N22

Abstract: Seed storability in rice (Oryza sativa L.) is an important agronomic trait. Two segregating populations with N22 (indica) as a common parent, viz. a set of 122 backcross-inbred lines (BILs) derived from the backcross Nanjing35 (japonica)/N22//Nanjing35 and another population comprising 189 recombinant inbred lines (RILs) from the cross of USSR5 (japonica) and N22, were studied to detect quantitative trait loci (QTL) controlling seed storability. Germination percentage (GP) was used to evaluate seed storability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Seed aging or deterioration in rice ( Oryza sativa L.) is a major problem for agronomic production and germplasm preservation (Lin et al, 2015; Gao et al, 2016; Yan et al, 2018). Kameswara Rao and Jackson (2008) suggested that the seed storability in different rice varieties was: indica>javanica>japonica.…”
Section: Discussionmentioning
confidence: 99%
“…Seed aging or deterioration in rice ( Oryza sativa L.) is a major problem for agronomic production and germplasm preservation (Lin et al, 2015; Gao et al, 2016; Yan et al, 2018). Kameswara Rao and Jackson (2008) suggested that the seed storability in different rice varieties was: indica>javanica>japonica.…”
Section: Discussionmentioning
confidence: 99%
“…Seed storability is a crucial factor for viability maintenance during storage ensuring proper seedling establishment and high yield in crops. Many studies have shown that seed storability is a complex trait with remarkable variation controlled by polygenes [6,7,9,11,12,13]. In the present study, a high-density linkage map has been developed in the relative large population of NIP/9311, which harbors 2864 bins with an average physical interval of 129.7 kb (Table S1).…”
Section: Discussionmentioning
confidence: 96%
“…For example, indica -type seeds maintained their viability longer than japonica -type seeds [4,5]. Using quantitative trait loci (QTLs) analysis and association mapping approaches, many research groups have identified numerous QTLs for seed storability in rice that were evaluated by natural storage or artificial aging [6,7,8,9,10,11,12,13]. Although there are several loci commonly detected across some populations, such as qRGR-1 on chromosome 1, qRGR3 on chromosome 3, qLG-7 on chromosome 7, qLG-9 on chromosome 9, and qSS11 on chromosome 11, most QTLs identified for seed storability are different in various genetic populations.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, qSL‐8 was different from qGP‐8 . In addition, qSL‐2 overlapped with the region of qSSnj‐2‐1 , a QTL for seed storability that was detected in BILs of Nanjing35/N22//Nanjing35 using germination percentage as an index after artificially ageing seeds (Lin et al., ). A few studies indicated that the regulation between artificial and natural ageing seeds might be controlled by different genes due to significant differences in physiological and biochemical characteristics (Ren, Peng, Tang, Xu, & Xing, ; Scgwenber & Bradford, ).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of molecular markers makes genetic dissection of seed longevity possible. To date, more than twenty QTLs associated with seed longevity have been identified using different populations derived from the crossing of subspecies (Hang et al, 2015;Li et al, 2012Li et al, , 2017Lin et al, 2015a;Miura, Lin, Yano, & Nagamine, 2002;Sasaki, Fukuta, & Sato, 2005;Xue et al, 2008). Miura et al (2002 used backcross inbred lines (BILs) derived from a cross between Nipponbare and Kasalath to identify three QTLs.…”
Section: Introductionmentioning
confidence: 99%